2005
DOI: 10.1200/jco.2005.06.055
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Familial Endometrial Carcinoma: A Manifestation of Hereditary Nonpolyposis Colorectal Cancer or a Separate Syndrome?

Abstract: Our study gives a minimum overall frequency of 2.1% (11 of 519) for germline MMR defects ascertained through EC in the index patients. The fact that only two of 23 families with site-specific EC (8.7%) had germline mutations in MMR genes suggests another as yet unknown etiology in most families with site-specific EC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 36 publications
5
100
1
3
Order By: Relevance
“…Factors that have delayed the elucidation of an exact frequency have primarily arisen from the diversity of study designs, including positive family history-only case designs (32 -35), MSI-type EC studies (36,37), and groups without definitive MMR mutation results, a limitation also associated with our current study. The largest study thus far of unselected EC patients (n = 543) concluded, after comprehensive mutation testing and consistent with two previous reports (11,35), that at least 1.8% of all EC could be attributed to Lynch syndrome (14). In that report, immunohistochemistry for MMR was used post hoc essentially to confirm MSI results, and investigations were not confined to the young-onset patient as is the case here.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Factors that have delayed the elucidation of an exact frequency have primarily arisen from the diversity of study designs, including positive family history-only case designs (32 -35), MSI-type EC studies (36,37), and groups without definitive MMR mutation results, a limitation also associated with our current study. The largest study thus far of unselected EC patients (n = 543) concluded, after comprehensive mutation testing and consistent with two previous reports (11,35), that at least 1.8% of all EC could be attributed to Lynch syndrome (14). In that report, immunohistochemistry for MMR was used post hoc essentially to confirm MSI results, and investigations were not confined to the young-onset patient as is the case here.…”
Section: Discussionsupporting
confidence: 62%
“…We also examined the family history of a first-degree relative with any type of cancer and found no significant difference between our two groups. In a previous study, Suomi et al (35) investigated the family history of 291 EC patients ages V60 years. They found that 45% (130 of 291) of patients in their study had at least one first-degree family member with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of all 24 tumor suppressor loci included in the assay All tumors displaying a reduction over 21% for one allele (i.e. having ratios below 0.8 or above 1.25) were regarded as having LOH, including 21 with 'strict LOH' (X40% reduction) and nine with 'putative LOH' (21-39% reduction; Ollikainen et al (2005)). ND, not determined.…”
Section: Resultsmentioning
confidence: 99%
“…The allele frequency ratios for tumor samples were divided by the allele frequency ratio of the corresponding normal sample. The thresholds for LOH were defined according to Ollikainen et al (2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation